COVID-19: Respon imunologis, ketahanan pada permukaaan benda dan pilihan terapi klinis - Komang Siska Lestari Sugitha (Intisari Sains Medis, 2020)
The massive spread of SARS-CoV-2 infection marks the introduction of the third highly pathogenic corona virus after SARS-CoV and MERS-CoV infections that have caught the world's attention. In Indonesia alone, as of 9 April 2020, 3,512 cases have been confirmed, 282 recovered, and 306 of them died. Covid-19 CFR varies in each country, and CFR increases with age, especially if the patients have comorbid disease. SARS-CoV-2 can be detected in various specimens, such as oropharyngeal, BAL, sputum, faeces, and blood, but not detected in urine. SARS-CoV-2 infects populations of various ages, but severe symptoms are not reported in children. The host immune response is the key in eradicating the virus, as well as playing a role in the uncontrolled inflammatory response or cytokine storm. This may be due to the lack of corona virus-specific T memory cells in children so that when infected with SARS- CoV-2, the immune and inflammatory response is not as severe as in adults or the elderly. The long-term immune response of COVID-19 is still a big question. There is no specific vaccine and therapy COVID-19 approved by the FDA.Aim: The literature review this time aims to provide the general features the infection of SARS-CoV-2.Conclusion: From all of the patients who confirmed Covid-19, most of them were adults and elderly, with an increased risk of mortality in elderly with comorbidities. To reduce false negative diagnostic, specimens should be taken from different sites, such as nasal, throat, faeces, blood, and BAL. Until now, there’s no specific therapy and vaccines against SARS-CoV-2 infection. Infeksi SARS-CoV-2 yang penyebarannya begitu masif menandai perkenalan virus corona ketiga yang sangat patogen setelah infeksi SARS-CoV dan MERS-CoV yang menyita perhatian dunia. Di Indonesia sendiri, per tanggal 9 April 2020, 3.512 kasus telah terkonfirmasi, 282 sembuh, 306 diantaranya meninggal dunia. CFR COVID-19 bervariasi di setiap negara, dan CFR meningkat seiring bertambahnya usia, terutama bila memiliki penyakit komorbid. SARS-CoV-2 dapat dideteksi di berbagai spesimen, seperti orofaringeal, BAL, sputum, feses, dan darah, tetapi tidak terdeteksi pada urin. SARS-CoV-2 menginfeksi populasi dari berbagai usia, tetapi gejala berat tidak dilaporkan pada anak-anak. Respon imun host merupakan kunci dalam eradikasi virus, sekaligus memegang peranan terjadinya respon inflamasi tidak terkontrol atau badai sitokin. Hal ini mungkin disebabkan oleh sedikitnya sel T memori spesifik virus corona pada anak-anak sehingga ketika terinfeksi SARS-CoV-2, respon imunitas dan inflamasi yang terjadi tidak separah pada dewasa atau usia lanjut. Respon kekebalan jangka panjang COVID-19 saat ini masih menjadi pertanyaan besar. Belum ada vaksin dan terapi spesifik COVID-19 yang disetujui FDA.Tujuan: Literatur ini dibuat bertujuan untuk memberikan gambaran umum mengenai infeksi virus SARS-CoV-2.Simpulan: Dari keseluruhan pasien yang terkonfirmasi Covid-19, sebagian besar adalah pasien dewasa dan usia tua, dengan resiko mortalitas semakin meningkat pada pasien usia tua yang memiliki komorbid. Untuk mengurangi hasil negatif palsu, diagnosis Covid-19 data ditegakkan dengan mengambil spesimen dari berbagai tempat, seperti nasal, faring, fees, Sarah, dan BAL. Hingga saat ini belim ada terapi dan vaksin spesifik untuk indeksi SARS-CoV-2.